2013
DOI: 10.1128/mcb.00074-13
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Mice Deficient in both KLF3/BKLF and KLF8 Reveals a Genetic Interaction and a Role for These Factors in Embryonic Globin Gene Silencing

Abstract: f Krüppel-like factors 3 and 8 (KLF3 and KLF8) are highly related transcriptional regulators that bind to similar sequences of DNA. We have previously shown that in erythroid cells there is a regulatory hierarchy within the KLF family, whereby KLF1 drives the expression of both the Klf3 and Klf8 genes and KLF3 in turn represses Klf8 expression. While the erythroid roles of KLF1 and KLF3 have been explored, the contribution of KLF8 to this regulatory network has been unknown. To investigate this, we have genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 107 publications
(156 reference statements)
3
29
0
Order By: Relevance
“…However, it has recently been shown that 2 members of the KLF family (KLF3 and KLF8) may be involved in regulating embryonic globin expression, and a knockout of these 2 transcription factors in erythroid cells de-represses embryonic globin synthesis. 41 Because expression of these 2 factors is driven by KLF1, it is possible that mutations in this protein might reduce KLF3 and KLF8, leading to derepression of embryonic globins. Further analysis of this pathway is warranted because preliminary studies in mice suggest that persistence of embryonic globin expression could ameliorate severe hemoglobinothathies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been shown that 2 members of the KLF family (KLF3 and KLF8) may be involved in regulating embryonic globin expression, and a knockout of these 2 transcription factors in erythroid cells de-represses embryonic globin synthesis. 41 Because expression of these 2 factors is driven by KLF1, it is possible that mutations in this protein might reduce KLF3 and KLF8, leading to derepression of embryonic globins. Further analysis of this pathway is warranted because preliminary studies in mice suggest that persistence of embryonic globin expression could ameliorate severe hemoglobinothathies.…”
Section: Discussionmentioning
confidence: 99%
“…CtBP2 interacts with the N-terminus of KLF3 and related KLFs to provide a repressor function. 71 Mice lacking both Klf3 and Klf8 fail to repress embryonic globin gene expression in vivo, 72 so regulation of CtBP2 could be an alternative mechanism by which KLF1 indirectly regulates embryonic and fetal globin gene silencing (ie, via "enabling" the repression functions of KLF3 and KLF8). We also found that KLF1 regulates SOX6, which plays a key role in definitive erythropoiesis and embryonic globin gene silencing.…”
mentioning
confidence: 99%
“…43,44 KLF8 knockout mice have normal erythroid parameters. 45 The KLF3/KLF8 double knockout causes embryonic lethality, and greater dysregulation of fetal liver gene expression than either single knockout. 45 The reduced number of E10.5 KLF1-/-KLF2-/-peripheral blood cells stems from a defect in erythroid precursor maintenance and maturation.…”
mentioning
confidence: 99%
“…45 The KLF3/KLF8 double knockout causes embryonic lethality, and greater dysregulation of fetal liver gene expression than either single knockout. 45 The reduced number of E10.5 KLF1-/-KLF2-/-peripheral blood cells stems from a defect in erythroid precursor maintenance and maturation. Primitive erythroid progenitor colonies (EryP-CFC) derived from E8.5 KLF1-/-embryos are similar in frequency but significantly smaller in size than wild-type.…”
mentioning
confidence: 99%